Quality assessment of clinical practice guidelines for perioperative care and use of GRADE: a systematic review protocol - Kantorová, Lucia; Kantor, Jiří; Búřil, Jiří; Búřilová, Petra; Slezáková, Simona; Nečas, Tomáš; Klugar, Miloslav (BMJ open, 2021)
INTRODUCTION: Perioperative care is a broad field covering an array of elective and emergency procedures. Clinical practice guidelines (CPGs) for perioperative care exist with various degrees of methodological quality. We intend to critically appraise them using AGREE II instrument and investigate the use of Grading of Recommendations, Assessment, Development and Evaluations (GRADE). METHODS AND ANALYSIS: We searched MEDLINE (Ovid), Epistemonikos, Cochrane Database of Systematic Reviews and PROSPERO and did not identify any similar systematic review in this area. We will search databases, repositories and websites of guideline developers and medical societies, including MEDLINE (Ovid), Embase (Ovid), DynaMed, the GIN international guideline library and registry of guidelines in development, BIGG international database of GRADE guidelines, ECRI Guideline Trust or National Institute for Clinical Evidence to identify all CPGs for perioperative care in an adult population in a general clinical setting. We will include CPGs, expert guidance, position papers, guidance documents and consensus statements published in the last 5 years by experts or international organisations that provide guidance or recommendations in the available full text with no geographical or language limitation. Excluded will be those containing only good practice statements. Two independent reviewers will perform critical appraisal using the AGREE II tool. The data presented in a narrative and tabular form will include the results of the critical appraisal for all identified CPGs for all AGREE II domains and an assessment of the use of the GRADE approach. ETHICS AND DISSEMINATION: Ethics approval is not required. We will disseminate the findings through professional networks and conference presentations and will publish the results.
Keywords: quality in health care; dospělí; Databases, Factual; Consensus; lidé; konsensus; Perioperative Care; perioperační péče; Systematic Reviews as Topic; protocols & guidelines; surgery; statistics & research methods; databáze faktografické; systém GRADE; Adult; GRADE Approach; systematický přehled jako téma; Humans